Promoting economic development through digitalisation: Impacts on human development, economic complexity, and gross national income - Namhla Xholo; Thobeka Ncanywa; Rufaro Garidzirai; Abiola John Asaleye (Administrative Sciences, 2025)
The advancement of digital technologies has become a transformative driver of economic development. Digitalisation is central to the global economy, enhances productivity, drives innovation, and promotes inclusive growth. Despite this potential, South Africa faces persistent challenges such as skills shortages, unemployment, poverty, and socioeconomic inequality. This study investigates the role of digitalisation in advancing economic complexity, human capital development, and gross national income in South Africa. A digitalisation index, constructed through Principal Component Analysis, ARDL models, and Granger causality analysis, provides insights into the short- and long-term impacts and causal relationship. The findings reveal that digitalisation and education significantly enhance human capital development in the long run, with digital infrastructure also driving immediate gains. For the gross national income model, digitalisation and education pose short-term pressures due to development expenditures, while institutional quality plays an important role in sustaining income. Economic complexity benefits positively from digitalisation over the long term, though short-term impacts stress the role of governance quality and infrastructure. Causality analysis further shows the interconnectedness of these variables, with digitalisation advancing economic complexity and human capital driving national income, reinforcing digitalisation. The results call for policies that align short-term developmental priorities with long-term sustainability. Investments in digital infrastructure, accessible education, and institutional frameworks are critical for building a skilled labour force while enhancing economic complexity and maintaining financial stability.
Keywords: 350; digitalisation; economic complexity; gross national income; human capital development